Toward a Single Reed Mouthpiece for the Oboe - CARRAL, Sandra; VERGEZ, Christophe; NEDERVEEN, Cornelis J. (Archives of Acoustics, 2011)
Reed woodwind instruments differ in both their geometry (mainly cylindrical or mainly conical) and their excitation mechanism (single or double reed). How much of the resulting sound is due to the single/double reed, and how much to the geometry of the instrument? Measurements done by Almeida et al. (J. Acoust. Soc. Am., 121, 1, 536–546, 2007) show that the flow vs pressure characteristic curve of an oboe reed is not that different from that of a clarinet reed, the only difference probably being due to pressure recovery inside the conical staple. Is it possible to make a single reed mouthpiece for an oboe, while keeping the conical staple, that would still give the oboe its characteristic sound? To find it out, a mouthpiece with the following characteristics was made: A standard clarinet B[ reed can be attached to it, its volume is approximately that of the missing part of the instrument cone, and a standard French oboe staple can be inserted to it, so that it can be inserted in the usual way in any french oboe. In this paper, the first prototype of the mouthpiece is shown. Also, a sound comparison of the oboe sounds played with this mouthpiece and a standard double reed by a professional player is presented.